Application of 18F-FDG PET-CT Simulation Localization in Radiotherapy of Recurrent Abdominal and Pelvic Tumors - JIN Long; XU Dameng; ZHOU Yuanyuan; YU Jiao (Zhongliu Fangzhi Yanjiu, 2022)
Objective To investigate the clinical application value of 18F-FDG PET-CT simulation localization in radiotherapy of recurrent abdominal and pelvic tumors. Methods 18F-FDG PET-CT was used to simulate positioning 38 patients with abdominal and pelvic tumors who relapsed after treatment.Based on both CT images and 18F-FDG PRT-CT, we drew up a systemic treatment plan and outlined the radiotherapy target area, and then compared the differences between the two methods. Results In 38 patients, 21.1%(3/8) of patients were found to have distal metastases outside the pelvic and abdominal cavity, and changed the systemic treatment plan.The radiotherapy target was altered in 34(89.5%) patients.The mean value of GTVPET-CT was 118.14cm3and the mean value of GTVCT was 148.53cm3(P=0.044). Conclusion For patients with recurrent abdominal and pelvic tumors, 18F-FDG PET-CT simulation localization treatment improves tumor re-staging, changes the integrated therapy for some patients, and makes the target area of radiotherapy more accurate.